The influence of the Javanese gamelan on selected piano works of Claude-Achille Debussy - Bird, Catherine (College of Music, 2015)
With rare exceptions, all the biographers of Claude Debussy mention the influence on the composer of the Javanese gamelan which appeared at the Universal Exhibition in Paris in 1889. Strangely, however, none of these historians discourse on the extent of this influence, nor on the way in which it is manifested in the works of Debussy. It is for this reason that this study was undertaken. ... This dissertation will examine the extent of the influence of just one of these elements: Oriental music, and the Javanese gamelan in particular. It will trace the influx into Europe of Eastern art forms and show how these affected the artistic state of Europe at the time: no study of Debussy is complete without taking into account the cultural milieu in which he moved, for he, more than any composer before him, was truly a product of his time. The Javanese game1ans which performed at the 1889 and 1900 Universal Exhibitions will be described here. Finally, with reference to selected piano works by Claude Debussy, the appearance and evolution of elements typical of the Javanese gamelan will be considered and an evaluation made of their role in the musical development of the composer, for as Rollo Myers remarks after his description of the Javanese music which Debussy heard, "... the experience thus gained undoubtedly tended to influence his musical thinking in the years to come ".